Pengaruh Biaya Produksi Terhadap Pendapatan Nelayan Ikan Asin (Desa Kupa, Kecamatan Mallusetasi, Kabupaten Barru) - Andi Sri Ulfiah; Darmawan; Nurhedah (Edupedia Publisher, 2024)
This research aims to analyze the effect of production costs on the income of salted fish fishermen in Kupa Village, Mallusetasi District, Barru Regency. The production costs analyzed include variable costs and fixed costs. This research used a quantitative descriptive approach with a population of 36 salted fish fishermen who were all sampled. Data was collected from October to December 2023 for three months and analyzed to calculate production costs and fishermen's income. The research results show that the largest variable cost is gasoline, with an average variable cost per month of IDR 4,465,667 and fixed costs of IDR 852,024. The average total production cost per month is IDR 5,317,691. The largest income comes from anchovy salted fish, with a total income for three months of IDR 295,500,000 and an average monthly income of IDR 8,208,333. The total profit fishermen earn is IDR 104,063,125, with an average monthly profit of IDR 2,890,642. This research shows that production costs significantly influence fishermen's income, and good cost management, especially variable costs, is very important to increase the income and profits of salted fish fishermen in Kupa Village.